Status of introduction and conservation in barley (Hordeum vulgare L.) - Tyagi, Vandana; Jacob, Sherry Rachel; Gupta, Kavita; Brahmi, Pratibha (Journal of Cereal Research, 2025)
Barley is important cereal crop and grown over a broad environmental range. There is a need to collect, conserve barley genetic resources to meet the known and unknown challenges of emerging diseases and climate change. For augmentation of diverse germplasm ICAR- National Bureau of Plant Genetic Resources (NBPGR) is the nodal institute with a well-established procedure and since its establishment in 1976 and a total of 80,124 accessions in barley were introduced/imported including trait specific/ value added accessions from different countries and International Institutes. Additionally, each year 200-3000 accessions are imported as international nurseries/ trials. International centre for Agricultural Research in Dry Areas (ICARDA) has the global mandate for improvement of barley and is doing rebreeding activities in barley. The new variability generated is made available to researchers users in form of International nurseries and trials and new form of variation in exotic material is made available through these nurseries/trials. The national Genebank at ICAR-NBPGR conserves over eight thousand accessions of barley of which more than one thousand five hundred accessions are of exotic origin. Access to these resources is regulated by various national and international instruments related to bio-diversity and agriculture. Access to barley germplasm from India is regulated by Biological Diversity Act, 2002. As barley is included in the multilateral system of the International Treaty on plant genetic resources for food and agriculture (ITPGRFA) and India has also designated 468 accessions to the MLS, the access to such designated accessions of barley is also made through the national focal point of the Treaty that is Department of Agricultural Cooperation and Farmers Welfare (DACFW). However access under the provisions of the Treaty is done after signing the Standard Material Transfer Agreement (SMTA), ensuring that the material accessed under the MLS of the treaty shall be freely available to others for use in research, breeding and training provided the third and subsequent parties are bound by the same conditions of the SMTA. Intellectual Property Rights (IPRs) cannot be claimed by the recipients on the material received from the MLS and if any commercial utilization is done, the benefits would be deposited in a trust fund of the Treaty. DOI.10.25174/2582-2675/2020/83213